GADAI DALAM ISLAM - Choirunnisak Choirunnisak; Disfa Lidian Handayani (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2020)
This research is a type of library research that focuses on qualitative data management with data analysis methods using descriptive analysis methods. Pawn in Islam is called Rahn. Islamic pawn shops will only benefit from the rental fees collected not in the form of interest or capital rents calculated from borrowed money.